1999
DOI: 10.1038/sj.ejhg.5200253
|View full text |Cite
|
Sign up to set email alerts
|

Screening for minor changes in the distal part of the human dystrophin gene in Greek DMD/BMD patients

Abstract: The distal part of the human dystrophin gene is characterised by particular features and seems to play an important functional role. Additionally in recent years several data have implicated minor mutations in this gene region in some patients with mental retardation (MR). In order to screen for pathogenic mutations at the distal part of the human dystrophin gene we have used single-strand conformation analysis of products amplified by polymerase chain reaction (PCR-SSCA) in 35 unrelated male Greek DMD/BMD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The only mutation in our study that was previously reported (19) is the DGA10716-10717 (Table 3). While the mutations are the same, the findings regarding the effect of mutation on mRNA and protein were very different.…”
Section: G a C T T C A A T A A A G A T A T G A A T G A A G A G A C mentioning
confidence: 62%
See 2 more Smart Citations
“…The only mutation in our study that was previously reported (19) is the DGA10716-10717 (Table 3). While the mutations are the same, the findings regarding the effect of mutation on mRNA and protein were very different.…”
Section: G a C T T C A A T A A A G A T A T G A A T G A A G A G A C mentioning
confidence: 62%
“…Eighteen deletion-negative BMD patients tested by means of multiplex PCR were included in this study (4,18). We identified seven causative mutations, of which six were novel (Table 3) (19). Two were novel missense mutations in the aminoterminal actin-binding domain of the dystrophin protein (R82P, L172H) ( Fig.…”
Section: Mutation-positive Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR primers and conditions for the exons containing the 11 known mutations (Table 1) are as previously described [14][15][16][17][18]. In order to maximize product yield DNA was amplified by using 50 ng of genomic DNA and performing 35 cycles of PCR in a final reaction volume of 50 ll.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Each class of exception has been convincingly explained by a distinct mechanism: (1) disruption of the "muscle-type" promoter and/or first exon results in phenotypic rescue by alternative promoter use in all tissues except the heart, and the consequence is cardiac rather than skeletal myopathy (Muntoni et al 1995), (2) frameshifting deletions early in the gene can allow in-frame translational re-initiation after abortive translation of the shortened cognate ORF, yielding an N-terminally truncated but otherwise full-length protein (Winnard et al 1995), (3) ORF-terminating mutations within the gene are sometimes associated with alternative splicing of exons bearing a point mutation (or adjacent to a rearrangement); this can restore the ORF in a proportion Fig. 1 A The 3' mutations of the dystrophin gene discussed in this paper (Barbieri et al 1996;Crawford et al 2000;Gardner et al 1995;Kekou et al 1999;Lasa et al 1997;Lenk et al 1993;McCabe et al 1989;Prior et al 1995;Roberts et al 1992). Dystrophin ORFs of the respective patients, drawn to scale against a schematic diagram of the corresponding regions of the message (labelled with exon numbers) and protein (labelled with known syntrophin and dystrobrevin interacting regions).…”
Section: Introductionmentioning
confidence: 97%